ISOLASI SENYAWA AKTIF âBRINE SHRIMPSâ AKAR Garcinia cowa Roxb FRAKSI ETIL ASETAT - arel, afdhil (LLDIKTI Wilayah X, 2015)
AbstractFlavonoid compound has been isolated as yellow crystalline which has melting point at 218-220ËC from root of Garcinia cowa Roxb. The compound was isolated by using column chromatography and characteristic with ultra violet spectroscopy, infrared spectroscopy, mass, 1H-NMR, and 13C-NMR.Â Â The indicated this compound was hegoflavon (B). Anticancer activities of aethyl acetat fraction and hegoflavon (B) using âBrine Shrimpsâ gave LC50 37,325 Âµg/ml and 1,95 Âµg/ml.